Phalangeal and metatarsal bone destruction by subungual squamous cell carcinoma complicated by Peptostreptococcus sp. infection in a dog – importance of histopathological diagnosis. - Barbosa Amaral, Camila; Pinto Romão, Mário Antônio; Reis Ferreira, Ana Maria (Medicina Veterinária, 2019)
The present article reports the case and complications of a canine with a subungual squamous cell carcinoma infected with Peptostreptococcus sp. whose initial diagnosis was erroneously considered as osteomyelitis, highlighting the importance of histopathological evaluation in digital lesions. A six-year-old female Rottweiler dog presented radiographic right metatarsal bone lysis after amputation of digit II phalanges due to a nonhealing ulcerated lesion. Amputated phalanges were fixed in formalin, but no histopathological evaluation was performed on that occasion. Osteomyelitis was suspected and clindamycin was prescribed. Bone lysis progressed up to tarsal bones even under antibiotic therapy, and due to its progression and severity, limb amputation was performed. Microbiological and histopathological evaluation of the limb respectively revealed Peptostreptococcus sp. and squamous cell carcinoma, the last one invading metatarsal bone, the same diagnosis later found in previously amputated phalanges. As shown on histopathological results, subungual squamous cell carcinoma advanced adjacent tissues and Peptostreptococcus sp. was considered an opportunistic agent. The patient recovered well and was healthy, with no evidence of metastasis a year and a half after amputation. The present case demonstrates the importance of histopathological evaluation to elucidate bone lesions and avoid complications, especially when digits are concerned.